Regional intellectual capital (RIC) indicators in Indonesia - Ihyaul Ulum; Mudrifah Mudrifah; Setyo Wahyu Sulistyono (Cogent Business & Management)
This study aims to identify acceptable RIC indicators for Indonesian conditions. The article discusses RIC indicators developed from NICs modified from Bontis’s and tailored to the requirements of Indonesia. The research was carried by utilizing data from IC disclosures in 38 Indonesian areas. There are three phases to the process. The first process is in-depth interviews, followed by focus group discussions (FGD), and finally by rediscussion. As a result, human capital in Indonesia, as measured by education, knowledge, and competence, is an example of capacity at the regional level. Customer or national loyalty, exposure to navigation, flexibility, and adaptation are key capital market points in Indonesia. Human capital in Indonesia is an example of capability, as measured by education, knowledge, and competence. Customer or national loyalty, exposure to navigation, flexibility, and adaptation are key capital market points in Indonesia. Meanwhile, the corporate environment, government presence, and knowledge transfer are used to assess process capital. GDP is a proxy for regional financial capital. The renewal capital index is based on basic research, R&D investment, and employer-university partnership. The model is unique in that it includes regional economic capital. The RIC indicators presented in Indonesia’s regions provide the user with numerous options, and the choice can be based on practical considerations such as the availability of needed data, the ease of implementation of the model, or the extent of complexity.